The Irie Classroom Toolbox: Mixed method assessment to inform future implementation and scale-up of an early childhood, teacher-training, violence-prevention programme - Marsha Bowers; Taja Francis; Helen Baker-Henningham; Helen Baker-Henningham (Frontiers Media S.A., 2022)
IntroductionViolence against children (VAC) is a violation of child rights, has high prevalence in low- and middle-income countries, is associated with long-term negative effects on child functioning, and with high economic and social costs. Ending VAC at home and at school is thus a global public health priority.MethodsIn Jamaica, we evaluated an early childhood, teacher-training, violence-prevention programme, (the Irie Classroom Toolbox), in a cluster-randomised trial in 76 preschools. The programme led to large reductions to teachers' use of VAC, although the majority of teachers continued to use VAC at times. In this paper, we describe a mixed-method evaluation of the Irie Classroom Toolbox in the 38 Jamaican preschools that were assigned to the wait-list control group of the trial. In a quantitative evaluation, 108 preschool teachers in 38 preschools were evaluated at pre-test and 91 teachers from 37 preschools were evaluated at post-test. One preschool teacher from each of these 37 preschools were randomly selected to participate in an in-depth interview as part of the qualitative evaluation.ResultsPreschool teachers were observed to use 83% fewer instances of VAC across one school day after participating in the programme, although 68% were observed to use VAC at least once across two days. The qualitative evaluation confirmed these findings with all teachers reporting reduced use of violence, but 70% reporting continued use of VAC at times. Teachers reported that the behaviour change techniques used to deliver the intervention increased their motivation, knowledge and skills which in turn led to improved child behaviour, improved relationships and improved professional well-being. Direct pathways to reduced use of VAC by teachers were through improved child behaviour and teacher well-being. The main reasons for continued use of VAC were due to barriers teachers faced using positive discipline techniques, teachers' negative affect, and child behaviours that teachers perceived to be severe.DiscussionWe describe how we used the results from the mixed-method evaluation to inform revisions to the programme to further reduce teachers' use of VAC and to inform the processes of training, supervision and ongoing monitoring as the programme is scaled-up through government services.